647 Management of Malignant Upper Urinary Tract Obstruction. (12th October 2021) - Lewis, F; Neal, N
Abstract: Background: Malignant Upper Urinary Tract Obstruction (MUUTO) is a common emergency presentation. These are often complex patients and require multiple specialty input to make time-critical decisions. There are currently no national guidelines for the management of MUUTO, a review was conducted to assess the management and outcomes of MUUTO. Aim: To agreed and review a pathway for patients with MUUTO in order to streamline patient care and to review the management. Method: The pathway was devised by several consultants at Oxford University Hospital. Through retrospective data collection, the outcomes over six months were reviewed. Results: Over the six-month period 49 interventions were performed for MUUTO; 44 Percutaneous Nephrostomy (PCN) and five cystoscopies with retrograde ureteric stents (RUS). Patients were admitted to urology in 45% of cases and oncology in 39%. The obstruction was located above the pelvis in 16 (33%) of the cases and within the pelvis in 25 (51%). The most common cancers causing obstruction were bladder cancer (41%), prostate (16%), and colorectal (14%). MDT advice was sought in 63% of cases. The mean time from diagnosis to the intervention was four days. Of the five retrograde inserted ureteric stents, four were unsuccessful and the patients proceeded to PCN. At the conclusion of data collection, 26 (53%) patients had died. Discussion: The most striking findings were the high failure rate of RUS and the overall poor prognosis of MUUTO. As such this review suggests that more patients should proceed directly to PCN for decompression.